Midlife Marital Dissolution and the Onset of Cognitive Impairment. (27th November 2020) - Brown, Susan L; Lin, I-Fen; Vielee, Alyssa; Mellencamp, Kagan A
Abstract: Background and Objectives: Marital dissolution has become more common in midlife with the doubling of the divorce rate among middle-aged adults. Guided by the stress model that stipulates losing economic, social, and psychological resources lowers well-being, we posited that midlife adults who experienced divorce or widowhood were at greater risk of cognitive impairment than the continuously married. Subsequent repartnering was expected to negate the increased risk. Research Design and Methods: We used data from the 1998–2016 Health and Retirement Study to estimate discrete-time event history models using logistic regression to predict cognitive impairment onset for men and women. Results: Roughly 27% of men who experienced spousal death in midlife went on to experience mild cognitive impairment by age 65. For women, experiencing divorce or widowhood was associated with higher odds of cognitive impairment onset although these differentials were accounted for by economic, social, and psychological resources. Men and women who repartnered after marital dissolution did not appreciably differ from their continuously married counterparts in terms of their likelihoods of cognitive impairment onset. Discussion and Implications: A stressful life event, midlife marital dissolution can be detrimental to cognitive well-being, placing individuals at increased risk of developing dementia in later life. The growing diversity of partnership experiences during the second half of life points to the continued importance of examining how union dissolution and formation shape health and well-being.